Optical reflectance contrast of micro- and nano-structures revealed with intravital micro-OCT - Chen, Si (Nanyang Technological University, 2020)
Optical coherence tomography (OCT) provides depth-resolved three-dimensional images allowing the visualization of subsurface microstructures over large areas in situ and thus is a promising tool for epithelial disease screening. However, it has generally been relegated to a nonspecific diagnostic tool because the optical reflectance (back-scattering) contrast in OCT images is poorly understood although some contrast agents are available for OCT. This thesis focuses on elucidating the microstructural and ultrastructural bases underlying optical contrast to explore if OCT could provide diagnostic information in epithelial tissues with specificity. We investigate the back-scattered intensity of different intracellular scatterers at the micrometer and nanometer scale using finite-difference-time-domain method numerically and cellular-resolution OCT (μOCT) experimentally. We uncover that there exist correlations between reflectance contrasts (optical reflectance intensity differences among structures) and intracellular scatterers, and clarify that the nuclei in the nonkeratinized stratified squamous epithelium are low-scattering in the core and high-scattering at the nucleocytoplasmic boundary while the scattering properties of cytoplasm is cell-type specific depending on its ultrastructural features. We further validate that these new understandings on reflectance contrast enable the characterization of precancerous lesions in OCT images with specificity, which may have a significant impact on the screening and surveillance of epithelial cancers. In addition, we also make an effort to optimize OCT imaging system by optimizing the spectral shape of the detected signal. We design a novel cost-effective interferometer-in-spectrometer scheme where the reference beam is spectrally shaped when passing through the zero-order diffraction channel of the grating prior to interfering with the sample light at the spectrometer input fiber tip. Therefore, the spectral modulations caused by the grating and the camera are compensated for by improvements in axial resolution by 10% and ranging depth by 25% without impairing the system sensitivity.